Between Islamic Morality and Legal Certainty: Political Compromise in Regulating Adultery and Non-Marital Cohabitation in Indonesia’s New Criminal Code - Rizki Maulana; Fouza Azwir Abdul Azis; Muammar Izazi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
The reformulation of articles concerning adultery and cohabitation in the new Criminal Code (Law No. 1 of 2023) raises fundamental questions regarding how Islamic values can be harmonized with national criminal law without undermining legal certainty and the protection of individual rights. This study aims to analyze the mechanisms for harmonizing Islamic values within the new Criminal Code, particularly in the articles on adultery and cohabitation, as well as to assess the relevance of legal politics in regulating public morality. The study employs a qualitative-descriptive approach with content analysis, relying on primary legal documents and secondary legal literature. The analysis is conducted thematically to evaluate the extent to which the new Criminal Code provides legal certainty, substantive justice, and protection of individual rights. The findings indicate the existence of a political compromise pattern reflected in the adjustment of sanctions, limitations in the scope of law enforcement, and interactions among legislators, law enforcement officers, and religious stakeholders. This study confirms that the new Criminal Code functions as an adaptive and proportional legal instrument, with significant implications for legal politics in Indonesia, particularly in harmonizing public aspirations, constitutional principles, and societal moral norms.